PERSEPSI GENERASI MILENIAL TERHADAP KEANGGOTAN DAN PARTISIPASI DALAM KOPERASI DI INDONESIA - Sucipto Sucipto (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Cooperatives in Indonesia play an important role as pillars of the people’s economy; however, millennial participation remains relatively low despite this group being the largest demographic within the productive age range. This study aims to analyze millennials’ perceptions of cooperatives and identify the factors that influence their engagement, including perceived benefits, social norms, and ease of participation. A quantitative approach with descriptive and explanatory designs was employed, involving an Indonesian millennial population of approximately 88 million individuals. The research sample consisted of 212 millennial respondents aged 25–40 years from various regions of Indonesia, collected through an online questionnaire based on the Theory of Planned Behavior. The findings indicate that perceived benefits, social norms, and ease of participation significantly contribute to millennial involvement in cooperatives, with social norms emerging as the most dominant factor. These results highlight that millennials’ motivation to join cooperatives is not only driven by economic benefits but is also strongly influenced by social support and the accessibility of cooperative services. The study recommends that cooperatives strengthen educational programs, enhance community-based engagement, and accelerate the adoption of digital innovations to attract millennial interest and ensure cooperative sustainability in the digital economy era.